Poligami Dalam Perspektif Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan Dan Hukum Islam (Studi Kasus Poligami di Surabaya) - Achmad Achmad (STAI Syaichona Moh. Cholil Bangkalan, 2016)
This paper starts from two question as; what do Surabaya community motivate polygamous? and how are the procedures of polygamy in the Marriage Law and Islamic law? This research was qualitative. Therefore, the data collected through the reading of the text of legislation and interviews with the subject of research as well as interviews with people who are competent in the field of the problems studied. Then the results were analyzed using descriptive analytical techniques. The results of this study explained that of the 120 cases of polygamy (officially and Sirri) in Surabaya, hence the reason/motivation and procedures polygamy in Surabaya can be concluded that there are several reasons as the basis of polygamists, there are 64 grounds on which to base polygamy in Surabaya, yet only 38 reasons (applicant) or only 59.3% of applicants who meet the criteria of reason in accordance with the legislation in force, and can be recommended to carry out polygamy. While the findings based on the procedure, which is used polygamists in Surabaya, to 64 cases of polygamy official, the phase of the inspection process in the PA Surabaya, there are 33 polygamists, or 51.5% of qualified and worthy to the next phase. While the remaining 31 polygamists or 48.4% did not qualify cumulative. Meanwhile, the phase of the ceremony, an official of the 64 cases of polygamy, it turns out not all polygamous marriages recorded in VAT and registered at KUA, but married Sirri as many as 9 polygamists or 14%, and there are polygamists who cancel for polygamy. While the number of polygamists who recorded a polygamous marriage in VAT, and is listed on the KUA as many as 47 polygamists or 73.5%.